2014
DOI: 10.1039/c3ce42068j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable growth of ZnO–ZnSe heterostructures for visible-light photocatalysis

Abstract: ZnO–ZnSe heterostructures for visible-light photocatalysis are fabricated via a two-step CVD process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The above analysis confirms that the as-synthesized ZnS has the structure of alternating WZ/ZB stackings, which may provide the possibility of its application in charge-separation areas, other than the pre-mentioned areas, since WZ ZnS and ZB ZnS form a staggered type-II band alignment. 21,38,39 …”
Section: Resultsmentioning
confidence: 99%
“…The above analysis confirms that the as-synthesized ZnS has the structure of alternating WZ/ZB stackings, which may provide the possibility of its application in charge-separation areas, other than the pre-mentioned areas, since WZ ZnS and ZB ZnS form a staggered type-II band alignment. 21,38,39 …”
Section: Resultsmentioning
confidence: 99%
“…The conduction band levels of ZnO and ZnSe are at−0.15 and−0.41 eV whereas, the valence band energy levels are at 3.05 and 2.2 eV, respectively. The valence band (VB) of ZnO is more positive than VB of ZnSe almost by 0.85 eV . Upon illumination with 350 nm wavelength, the electrons present in the VB of ZnO and ZnSe get excited to respective conduction band (CB), there could be two probabilities for electron‐hole pair recombinations.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO‐based nanostructures attracted increasing interest, because the properties of ZnO‐based nanostructures can be tailored by changing the morphology, structure and size, or modifying surface with coatings of other materials. Considerable efforts have been devoted for synthesis of ZnO nanostructures including nanorods, nanobelts, nanodisks, nanowires and hierarchical structures [24] etc. Moreover, it is reported that one dimensional nanostructures improve the charge carrier mobility which in turn helps to minimize the electron–hole recombination leading to the higher photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, heterojunction of a ZnO/ZnS double layer can convert UV light into conducting carriers capable of detecting UV photons. Toward this goal, coreshell heterostructures such as ZnO-TiO 2 [2], ZnO-SnO 2 [3], ZnO-ZnSe [4], and ZnO-ZnS [5] have been successfully constructed in the past. In addition, 1D ZnO/ZnS nanostructures can facilitate the rapid transfer of photogenerated electron-hole pairs [6,7].…”
Section: Introductionmentioning
confidence: 99%